Pengaruh Pengungkapan Corporate Social Responsibility dan Good Corporate Governance Terhadap Nilai Perusahaan LQ45 - Fera Lufhidarani Pranita; Maria Evy Purwitasari; Widiyono Widiyono; Mohammad Sigit adi Nugraha; Muntasir Muntasir (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine and analyze the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) disclosures on the value of LQ45 companies. This research applied purposive sampling with specific criteria, yielding 140 observations. The study utilized secondary data sourced from the Indonesia Stock Exchange (IDX) website. Data were analyzed using descriptive statistics and multiple linear regression analysis. The findings indicate that CSR disclosure, institutional ownership, managerial ownership, and the board of commissioners have a significant positive effect on firm value. In contrast, the audit committee variable shows no significant effect on corporate value.